The impact of knowledge on recurrent gastritis episodes in adolescents: A study at Subang Hospital - Oktavia, Leli; Imran, Fadil (Program Studi Keperawatan, Politeknik Negeri Subang, 2025)
Background: Gastritis is a common gastrointestinal disorder among adolescents, influenced by unhealthy lifestyle choices, stress, and inadequate knowledge about prevention. Recurrent episodes significantly affect adolescents' quality of life, academic performance, and overall health. Purpose: This study aimed to analyze the relationship between adolescents' knowledge about gastritis and the recurrence of gastritis episodes at Subang Hospital. Methods: A cross-sectional study was conducted involving 70 adolescents aged 12–18 years who had been diagnosed with gastritis. Data were collected using validated questionnaires assessing knowledge about gastritis and medical records to confirm recurrence. Statistical analysis was performed using chi-square tests to determine the association between knowledge levels and recurrence rates. Results: The findings indicated a significant relationship between knowledge levels and gastritis recurrence (p < 0.05). Adolescents with low knowledge levels were more likely to experience recurrent gastritis episodes compared to those with higher knowledge. Female participants demonstrated slightly better knowledge but reported higher recurrence rates, possibly linked to stress-related factors. Conclusion: This study highlights the critical role of knowledge in preventing recurrent gastritis among adolescents. Comprehensive health education programs that address knowledge gaps, promote healthy behaviors, and incorporate stress management strategies are essential to reducing the prevalence of gastritis recurrence in this age group.